2012
DOI: 10.1007/s10461-012-0154-9
|View full text |Cite
|
Sign up to set email alerts
|

At the Edge? HIV Stigma and Centrality in a Community’s Social Network in Namibia

Abstract: Social network analysis was used to examine the relationship between HIV/AIDS stigmatization, perceived risk, and centrality in the community network (via participation in community groups). The findings from respondents in Keetmanshoop, Namibia (N = 375) showed an interaction between stigma and risk perceptions: those who perceived higher HIV risk and stronger HIV stigma participated in fewer community groups and participated in groups with members who participated less widely across the network. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Such misclassification would weaken the observed association between experiences of stigmatization and the perception of anticipated stigma. Additionally, previous studies have shown that individuals with ulcerative colitis [ 54 , 55 ] and acquired immunodeficiency syndrome [ 56 , 57 ] are more likely to experience stigma; however, we did not consider these diseases in our analysis because the necessary information was not collected in the survey. Third, those who are indifferent to COVID-19 may have been reluctant to complete this survey, because it is designed as a survey measuring the impact of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Such misclassification would weaken the observed association between experiences of stigmatization and the perception of anticipated stigma. Additionally, previous studies have shown that individuals with ulcerative colitis [ 54 , 55 ] and acquired immunodeficiency syndrome [ 56 , 57 ] are more likely to experience stigma; however, we did not consider these diseases in our analysis because the necessary information was not collected in the survey. Third, those who are indifferent to COVID-19 may have been reluctant to complete this survey, because it is designed as a survey measuring the impact of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Alters may still keep their previous relationship with ego, but reduce the amount of interaction upon learning of an ego's HIV status or association to a HIV positive person (Liu et al, 2009). Similarly, egos may also reduce contact frequency with alters due to fear of stigma and discrimination from alters once their HIV status or association with a HIV positive person is disclosed (Smith, Rossetto, & Peterson, 2008). Frequent contact was associated with less network stigma among both PLWHAs and caregivers, but the relationship was only statistically significant among caregiver egos.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that concerns about stigma are associated with reductions in test and treatment-seeking behavior, disclosure of HIV status, the level of social support solicited and received as well as personal identity and esteem [21,22]. Secrecy is therefore critical in community where HIV or TB till suffer social stigmatization [23]. In our study area, it was found that patients shun their testing and treatment facilities by fear for being discriminated against if they are labeled as infected with TB/HIV.…”
Section: Discussionmentioning
confidence: 99%